Pengaruh Insentif Dan Motivasi Kerja Terhadap Kinerja Karyawan PT Fotile Electrical Appliance Indonesia Wilayah Jakarta: The Effect of Incentives and Work Motivation on Employee Performance at PT Fotile Electrical Appliance Indonesia in the Jakarta Area - Aisiyah Annisa Mahfudloh; Eka Dyah Setyaningsih (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
Fotile Electrical Appliance Indonesia Jakarta Region considers employee performance as an important factor in supporting the achievement of company objectives. Therefore, optimal human resource management is required through the provision of fair incentives and the enhancement of work motivation. This study employs a quantitative research method with a survey approach. The population of this study consists of all employees of PT. Fotile Electrical Appliance Indonesia, with a total of 51 respondents selected using a saturated sampling technique. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination with the assistance of SPSS Statistics 25 software. The results of the study indicate that incentives partially have a positive and significant effect on employee performance. Work motivation also has a positive and significant effect on employee performance. Simultaneously, incentives and work motivation have a significant effect on employee performance at PT. Fotile Electrical Appliance Indonesia Jakarta Region. These findings indicate that appropriate incentive provision and increased work motivation can optimally improve employee performance.